Pattern recognition 33rd DAGM Symposium, Frankfurt/Main, Germany, August-September 2, 2011. Proceedings - Mester, Rudolf; Felsberg, Michael; SpringerLink (Online service). (Berlin New York Springer, 2011)
This book constitutes the refereed proceedings of the 33rd Symposium of the German Association for Pattern Recognition, DAGM 2011, held in Frankfurt/Main, Germany, in August/September 2011. The 20 revised full papers and 22 revised poster papers were carefully reviewed and selected from 98 submissions. The papers are organized in topical sections on object recognition, adverse vision conditions challenge, shape and matching, segmentation and early vision, robot vision, machine learning, and motion. The volume also includes the young researcher's forum, a section where a carefully jury-selected ensemble of young researchers present their Master thesis work.
Electronic reproduction.
Keywords: Pattern perception -- Congresses; Pattern recognition systems -- Congresses; Computer vision -- Congresses; Electronic books